Gender Role Analysis of Mulan and Bori Khan in Mulan 2020 Film - Surya Citra; Poppy Febriana (Universitas Muhammadiyah Sidoarjo, 2022)
Gender is an access in determining our choices regarding education, health, life expectancy, and freedom of movement. These biological differences provide indications and implications that the two sexes have different roles and tasks. These stereotypes also make the film world gave birth to feminist films. The film Mulan 2020 is the result of that stereotype. The purpose of this study was to determine the depiction of the gender roles of men and women in the characters of Mulan and Bori Khan in the film Mulan 2020. This research is a descriptive qualitative type of research using the semiotic analysis method of Charles S. Peirce. semiotic analysis of Charles S. Peirce To explain the icon (icon), index (index) and symbols (symbol) in the film Mulan 2020. The results of this study indicate that the gender roles of men and women in the film Mulan 2020 still refer to the socio-cultural structure that There are, such as men who can provide a living for the family, while women as wives are in charge of taking care of children and taking care of the household.